Identifikasi Berita Black Campaign Bersama Polsek Beringin Melalui Kegiatan Pengabdian Pengembangan Sistem SIHox - Anita Sindar; Ravindran; Sumitra Dewi (Jurnal Pengabdian Nasional (JPN) Indonesia, 2023)
People tend to use Internet features to respond to social media or update their opinions without considering the consequences of the opinions expressed. Issues identified include low public awareness, checking the truth and authenticity of news, and being more careful when sharing content on social media and browsing the internet. A fundamental contribution to the target audience in implementing community services is building a system for identifying black campaign messages. News analysis, which falls under Black campaign, is performed interactively through a process of reduction, data viewing, and validation. The system is systematically developed through the phases of system analysis (analyst), system construction (construction), coding (coding), system test (test), and system maintenance (maintenance). After the SIHox application was socialized and simulated, it was found that it took Beringin Police a very short time to identify online messages containing black campaigns. The system simulation success rate was 87% and the service implementation team had a performance score of 90.